Use of a smartphone electrocardiogram to diagnose arrhythmias during exercise in athletes: a case series. Issue 4 (23rd March 2022) - Jewson, Jacob L; Orchard, John W; Semsarian, Chris; Fitzpatrick, Jane; La Gerche, Andre; Orchard, Jessica J
Abstract: Background: While athletes are generally very fit, intense exercise can increase the risk of atrial fibrillation. Moreover, other arrhythmias such as atrial flutter or supraventricular tachycardia can cause distressing, exercise-related symptoms. Given symptoms are infrequent and may occur during intense exertion, traditional monitoring devices are often impractical to use during exercise. Smartphone electrocardiograms (ECGs) such as the Alivecor Kardia device may be the portable and reliable tool required to help identify arrhythmias in this challenging population. This case series highlights the use of such devices in aiding the diagnosis of arrhythmias in the setting of exercise-related symptoms in athletes. Case summary: The six cases in this series included one elite non-endurance athlete, two elite cricketers, one amateur middle-distance runner, and two semi-elite ultra-endurance runners, with an age range of 16–48 years. An accurate diagnosis of an arrhythmia was obtained in five cases (atrial fibrillation/flutter and supraventricular tachycardias) using the smartphone ECG, which helped guide definitive treatment. No arrhythmia was identified in the final case despite using the device during multiple symptomatic events. Discussion: The smartphone ECG was able to accurately detect arrhythmias and provide a diagnosis in cases where traditional monitoring had not. The utility of detecting no arrhythmia during symptoms in one case was also highlighted, providing the athlete with the confidence to continue exercising. This reassurance and confidence across all cases is perhaps the most valuable aspect of this device, where clinicians and athletes can be more certain of reaching a diagnosis and undertaking appropriate management.